2019
DOI: 10.1002/pd.5496
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PGT‐M and PGT‐SR outcomes at a Canadian fertility clinic

Abstract: Objective Outcomes from in vitro fertilization (IVF)/intrauterine insemination (ICSI) cycles for patients who underwent preimplantation genetic testing for monogenic/single gene (PGT‐M) and structural chromosome rearrangements (PGT‐SR) patients were reviewed. Patients pursuing PGT‐M and PGT‐SR often do not have pre‐existing fertility issues and therefore may have uncertain expectations of successful outcomes. Before pursuing PGT‐M and PGT‐SR, patients require evidence‐based counseling regarding the probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The lowest number of embryos suitable for transfer (16%) and associated outcome (clinical pregnancy rate of 32% per transfer or 16 % per started cycle) are observed in our subset of cycles with HLA matching (De Rycke et al 2020). Our results are in line with those of a Canadian PGT centre reporting ongoing pregnancies rates of 49% for PGT-M and 43% for PGT-SR (Butler et al 2019). It is obviously difficult to compare clinical outcomes between individual centres because of varying factors such as maternal age, indication type or differences in genetic testing and IVF procedures.…”
Section: Clinical Outcomesupporting
confidence: 86%
“…The lowest number of embryos suitable for transfer (16%) and associated outcome (clinical pregnancy rate of 32% per transfer or 16 % per started cycle) are observed in our subset of cycles with HLA matching (De Rycke et al 2020). Our results are in line with those of a Canadian PGT centre reporting ongoing pregnancies rates of 49% for PGT-M and 43% for PGT-SR (Butler et al 2019). It is obviously difficult to compare clinical outcomes between individual centres because of varying factors such as maternal age, indication type or differences in genetic testing and IVF procedures.…”
Section: Clinical Outcomesupporting
confidence: 86%
“…26 MB and above can be recognized reliably. 27 With this method, the time to have a healthy baby is shorter and it provides great benefits to both the family and the society.…”
Section: Resultsmentioning
confidence: 99%
“…Different small studies have investigated the outcome of PGT-M and have shown a CLBR ranging from 28.6% to 48.9% (Butler et al, 2019;Zanetti et al, 2019). The latest ESHRE consortium mentioned a CLBR of 24% for PGT-M (Coonen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%